Molecular identification and characterization of canine Hepatozoon species from Brazil - Rubini, A. S.; Paduan, K. D.; Cavalcante, G. G.; Ribolla, PEM; O'Dwyer, L. H. (Springer, 2005)
Canine Hepatozoon species from Brazil was molecular identified and characterized for the first time. From 31 dogs, 7 were positive for blood smear examination and 21 positive for PCR. Partial sequences of the 18S rRNA gene from eight naturally infected dogs were analyzed. Sequences revealed that Brazilian Hepatozoon is closely related with the Japanese Hepatozoon, that has 99% nucleotide identity with Hepatozoon canis from Israel, and different from Hepatozoon americanum. These results indicate that the canine Hepatozoon species from Brazil is H. canis.